Editorial for the Special Issue “Mathematical Modelling in Drug Delivery” - Fjóla Jónsdóttir (Pharmaceutics)
This Special Issue highlights the essential role of mathematical modelling in pharmaceutical research, particularly in the development and optimization of drug delivery systems [...]